Librarian's guide to online searching - Bell, Suzanne S. (Libraries Unlimited, 2006)
In this Internet age, database users soon learn how invaluable search strategies and effective search skills can be in the quest for information. This book suggests ways to obtain these skills while providing a general introduction to searching online environments. Starting with historical background, the author discusses database structure--records, fields, and indexes--and continues exploring basic search concepts, including Boolean logic, controlled vocabulary, proximity searching, and truncation. Subsequent chapters focus on commercial databases in specific subject areas. Other chapters examine information-seeking behaviors, reference interviews, database evaluation, and teaching others about databases. The content is practical, user-friendly, and enhanced by screen shots, exercises, and supplementary materials. Full of helpful advice and insightful commentary, this text is an outstanding reference tool (Editorial Reviews)